Sézary Syndrome with CD4/CD8 Double-Negative Neoplastic T Cells in Peripheral Blood - Yuki Kageyama; Kenshiro Tsuda; Yuma Nato; Keiki Nagaharu; Kazutaka Suzuki; Akihiko Sawaki; Hiroyuki Miyashita (Case Reports in Hematology)
Sézary syndrome is a rare leukemic type of cutaneous T-cell lymphoma characterized by the presence of neoplastic T cells with cerebriform nuclei (Sézary cells) in the skin, lymph nodes, and peripheral blood. Typical Sézary cells have a CD3+CD4+CD8– phenotype; however, in cases of the aberrant loss of antigens on Sézary cells, especially the loss of critically important T-cell antigens such as CD4, there is a possibility of misdiagnosing the disease or underestimating the tumor burden of the disease. Here, we report a rare case of Sézary syndrome with CD4/CD8 double-negative Sézary cells in the peripheral blood. Most of the Sézary cells in the peripheral blood had lost CD4 expression, and we diagnosed the disease and evaluated the tumor burden by multicolor flow cytometry. Intriguingly, the Sézary cells showed a typical CD4+CD8–CD7– phenotype in the skin even though the cells in the peripheral blood lacked CD4. The patient responded well to treatment with bexarotene and narrow-band ultraviolet B therapy. Analysis by multicolor flow cytometry is essential to diagnose this rare type of Sézary syndrome and evaluate the tumor burden.